Police Department Investments in Information Technology Systems Challenges Assessing Their Payoff - Jackson, Brian A. (RAND Corporation, 2014)
As local governments face declining revenues, budget tightening has presented police departments with challenging questions about how to deliver public safety more efficiently. In many jurisdictions, chiefs have adopted new technologies to reduce manpower costs. To examine the cost-effectiveness of doing so, the authors developed a model describing how information technology and policing activities work together to produce key policing outcomes.